Is the Romer Hypothesis valid for Newly Industrialized Countries? Evidence from panel ARDL - Çelik, Hüseyin; Alev, Nigar; Erdemli, Muhyettin (Economic Journal of Emerging Markets, 2024)
Purpose ― This study investigates the effect of trade openness on inflation, referred to as the Romer hypothesis, for Newly Industrialized Countries (NICs) from 1990 to 2022.Methods ― It uses a panel ARDL method and the Dumitrescu-Hurlin (2012) causality test. Economic growth, credit, and money supply are included in the model as independent variables. Findings ― The findings reveal no statistically significant long-term and short-term relationships between trade openness and inflation. However, money supply has statistically significant positive effects on inflation in the long run, while economic growth and credit exhibit no statistically significant impact. In the short run, money supply and economic growth reduced inflation. According to the Dumitrescu-Hurlin (2012) panel causality test, a bidirectional relationship exists between inflation and economic growth, money supply, and credit, while a unidirectional relationship is observed between inflation and trade openness. Implications ― Reducing the external dependency of sectors that rely on imported inputs is necessary to mitigate the adverse effects of trade openness on inflation in NICs. It is crucial to ensure that monetary policy helps align money supply and credit expansions with real sector trends.Originality ― This research is pioneering in its focus on testing the Romer hypothesis for Newly Industrialized Countries (NICs).